The Qur'an's Ideal Teacher Profile - Amirrudin MS (Rahis Cendekia Indonesia, 2023)
The point of this investigate is to investigate the Qur'anic concept of an perfect instructor profile. The Qur'an, as God's wonderful word, is exceedingly critical when utilized as an perfect parameter and, clearly, as a ponder protest. This inquire about utilizes a comprehensive survey of the writing and a subject elucidation approach. The comes about show that the Qur'an's wording for instructors is particularly far reaching; the term